2021
DOI: 10.1097/corr.0000000000001803
|View full text |Cite
|
Sign up to set email alerts
|

Is the Anterior Injection Approach Without Ultrasound Guidance Superior to the Posterior Approach for Adhesive Capsulitis of the Shoulder? A Sequential, Prospective Trial

Abstract: Background Shoulder injections for conditions such as adhesive capsulitis are commonly performed and can be administered through image-based or landmark-based injection approaches. Ultrasound-guided injections are widely used and accurate because ultrasound allows real-time visualization of the needle and injected contrast. Landmark-based injections would be advantageous, if they were accurate, because they would save the time and expense associated with ultrasound. However, few prospective studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Combined with the cost of time and money due to ultrasound-guided injection, it remains controversial whether ultrasound-guided technology is worth recommending ( 24 , 25 ). The current study used a modified AA for injection without ultrasound guidance, which has been proven to have the same accuracy for the glenohumeral joint as the standard PA ( 13 ). Using the acromioclavicular joint as a reference, this approach can accurately and quickly complete the injection process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Combined with the cost of time and money due to ultrasound-guided injection, it remains controversial whether ultrasound-guided technology is worth recommending ( 24 , 25 ). The current study used a modified AA for injection without ultrasound guidance, which has been proven to have the same accuracy for the glenohumeral joint as the standard PA ( 13 ). Using the acromioclavicular joint as a reference, this approach can accurately and quickly complete the injection process.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior approach group. As described by Rijs et al ( 13 ), the patient was placed in the sitting position, the upper limb was placed on the thigh on the same side and rotated outward as much as possible, and the elbow joint was placed in the flexion position. The in vitro anatomical landmarks of the shoulder joint were touched in order, and the coracoid process, the inner and outer edges of the acromion, the anterolateral angle of the acromion, the spine of the scapula and the acromioclavicular joint were marked with a pen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current sequential prospective study by Rijs et al [11] demonstrated an effective technique for intraarticular corticosteroid injections for adhesive capsulitis without the aid of imaging. The authors studied 95 patients comparing a new anterior approach versus posterior approach for intraarticular injections using anatomic landmarks by two experienced surgeons.…”
Section: Where Are We Now?mentioning
confidence: 99%